PENGARUH ECONOMIC VALUE ADDED (EVA), PROFITABILITAS, KEBIJAKAN DIVIDEN DAN PERTUMBUHAN PENJUALAN TERHADAP HARGA SAHAM (Studi Empiris pada Perusahaan Manufaktur di BEI Periode 2011-2013) - Bhagas Adhitya Ardia Pratama; Agus Purwanto (Diponegoro Journal of Accounting, 2014)
This study conducted to analyze the effect of variable Economic Value Added (EVA), Profitability, Dividend Policy, and Sales Growth to the Stock Prices on manufactur industies listed on Indonesian Stock Exchange from 2011 - 2013. The sampling technique used is purposive sampling and number of samples used is 100 from manufactur industries. Variables used in this study are variable Economic Value Added (EVA), Profitability (ROE), Dividend Policy (DPR), and Sales Growth as an independent variable; Stock Prices as an dependent variable; and Firm Size as an control variable. The analysis technique used are multiple linier regression. The result showed that Economic Value Added (EVA) has positive and not significantly impacted the stock prices. Profitability (ROE) has positive and significant impact to the stock prices. Dividend Policy (LnDPR) has negative and significant impact to the stock prices. Sales Growth has negative and not significantly impacted the stock prices Meanwhile Firm Size (LnAsset) has positive and significant impact to the stock prices.